Agglomeration Economies and Growth in Italian Local Labour Systems 1991-2001 - Raffaele Paci; Stefano Usai (European Regional Science Association (ERSA), 2005)
In the recent years a vast body of literature has analysed the role of agglomeration economies on industry location and growth. Such literature has, however, paid not too much attention to the wider scenario where such phenomena are rooted, that of an ongoing process of structural change which is transforming our economies from manufacturing to service ones. The main objective of this paper is to assess the role of a large set of potential determinants of the process of local agglomeration of economic activity distinguishing between manufacturing and service sectors and also to analyse the issue of spatial association of the local growth process. We focus on the case of Italy making use of a very ample database on socio-economic indicators for 784 Local Labour Systems and 34 sectors over the period 1991-2001. Our database covers both the manufacturing and the service sectors so that the whole economic system is considered. Our econometric results show that local growth in Italy is not a homogeneous process. On the contrary, it is characterized by significant differences across macro regions and especially across sectors. Among the most important determinants of local industry growth, it is worth mentioning the positive role of the diversity externalities. We also find robust evidence of the negative influence of specialisation externalities on labour dynamics at the local industry level. Moreover, we have assessed the effects of other determinants of local growth like human capital, social environment and network externalities. Finally, the presence of spatial autocorrelation is detected for the aggregate economy and also in several sectors and therefore dynamic spatial models have been estimated.
Keywords: 330